2020
DOI: 10.1177/0031512520973515
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Modulated Emotion and Facial Masking Encounter on Personal Distance

Abstract: In this study, we examined the effects of participants’ emotional states on personal space when an approaching person’s face was either masked or unmasked. We used the participants’ uncomfortable stop-distance as our method of measuring personal space. Inducing a positive emotion narrowed perceived personal space, whereas inducing a negative emotion widened personal space. For both positive and negative emotions, the perceived interpersonal distance was shorter when the approaching face was unmasked than maske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…First, as expected, participants were fastest when seeing individuals with a face mask, but not engaged in an interaction by shaking hands, slightly within and outside the peripersonal space (50–90 cm) as approaching the most appropriate distance for communication in Germany 63 . These results are in line with most of the previous studies 23 , 27 , 39 , 40 and only contradict the very early ones 36 , 37 . This can indicate that human perception of distances and masks has changed since the early days of the pandemic: the mask is no longer a symbol of danger but rather of protection.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…First, as expected, participants were fastest when seeing individuals with a face mask, but not engaged in an interaction by shaking hands, slightly within and outside the peripersonal space (50–90 cm) as approaching the most appropriate distance for communication in Germany 63 . These results are in line with most of the previous studies 23 , 27 , 39 , 40 and only contradict the very early ones 36 , 37 . This can indicate that human perception of distances and masks has changed since the early days of the pandemic: the mask is no longer a symbol of danger but rather of protection.…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with the studies by Cartaud and colleagues 23 , Calbi and colleagues 39 , Sakuma and Ikeda 27 and Welsch and colleagues 38 , we predict that the further individuals are in the pictures, the faster participants’ reaction times will be (positivity bias) (H1). In addition, we predict faster reaction times for pictures with a face mask compared to pictures without a face mask (positivity bias) (H2).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study reported that those who interacted with those who wore PPE experienced negative impacts on their psychological health, with increasing levels of anxiety. Additionally, four articles assessed for psychological factors and described similar findings (Kratzke et al 2021 ; Sakuma and Ikeda 2021 ; Thiagarajan et al 2021 ; Wong et al 2013 ). PPE that occluded a part of the face resulted in negative psychological impacts, specifically increasing stress, fatigue, and perceiving someone who wore PPE in a more negative light.…”
Section: Resultsmentioning
confidence: 84%
“…Most of these articles assessed the impact on speech intelligibility, facial and emotion recognition, and listening effort when PPE is worn. Studies also evaluated the impact on psychological health factors, such as stress, fatigue, and emotional state (5 articles, 19%) (Hoedl et al 2020 ; Kratzke et al 2021 ; Sakuma and Ikeda 2021 ; Thiagarajan et al 2021 ; Wong et al 2013 ). Two articles investigated the effect of PPE use on psychological illness symptoms, specifically anxiety and depression (2 articles, 8%) (Emanuel et al 2017 ; Tavakolizadeh et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%